Association between nonadherence to cardiovascular risk factor medications after breast cancer diagnosis and incidence of cardiac events. Issue 7 (8th January 2020) - Hershman, Dawn L.; Accordino, Melissa K.; Shen, Sherry; Buono, Donna; Crew, Katherine D.; Kalinsky, Kevin; Trivedi, Meghna S.; Hur, Chin; Hu, Jianhua; Unger, Joseph M.; Wright, Jason D.
Abstract : Background: Cardiovascular disease (CVD) is the leading cause of death among patients with early‐stage breast cancer (BC), but adherence to cardiovascular disease risk factor (CVD‐RF) medications is reported to be poor in BC survivors. The objective of the current study was to determine the association between nonadherence to CVD‐RF medications and cardiovascular events in BC survivors. Methods: The authors included patients with stages I to III BC from the Surveillance, Epidemiology, and End Results (SEER)–Medicare database who had Medicare part D coverage and who were taking at least 1 CVD‐RF medication prior to their BC diagnosis (2008‐2013). Logistic regression was performed to define factors associated with nonadherence. Cox regression was used to calculate the association between nonadherence and new cardiac events after treatment. Results: Among 15, 576 patients included in the current analysis, 4797 (30.8%) were nonadherent to at least 1 category after the initial BC treatment period. Black race, greater comorbidity burden, more advanced cancer stage, hormone receptor–negative status, and receipt of chemotherapy were found to be associated with nonadherence. Nonadherence after treatment demonstrated a trend toward an increased risk of a subsequent cardiac event (hazard ratio [HR], 1.15; 95% CI 1.00‐1.33 [ P = .06]). This effect size increased with nonadherence to a greater number of medications ( P < .01). There was an increased risk of experiencing a cardiac event noted with becoming nonadherent to hypertension medications (HR, 1.33; 95% CI, 1.18‐1.51 [ P < .0001]), hyperlipidemia medications (HR, 1.21; 95% CI, 1.05‐1.40 [ P = .009]), and diabetes medications (HR, 1.31; 95% CI, 1.10‐1.56 [ P = .003]). Conclusions: Nonadherence to CVD‐RF medications after treatment of BC is associated with an increased risk of a cardiac event. Improving outcomes and reducing morbidity after a diagnosis of BC requires attention to non‐BC conditions. Abstract : Nonadherence to cardiovascular disease risk factor medications after treatment of breast cancer is common. It is concerning that in the current study, nonadherence appears to result in an increased risk of a cardiac event. Improving outcomes and reducing morbidity after a diagnosis of breast cancer require attention to nonbreast cancer conditions.